Shearing Effect on Aggregation Behaviour of Hydrophobically Associating Polyacrylamide - Guo, Guang-Fan; Ye, Zhong-Bin; Zhao, Wen-Sen; Chen, Hong; Shu, Zheng (Asian Journal of Chemistry, 2014)
Hydrophobically associated polyacrylamide solutions were sheared by the waring blender at different speeds. Hydrophobically associated polyacrylamide solutions after being sheared were investigated by the viscometry using Ubbelohde viscometer, static light scattering, dynamic light scattering and atomic force microscopy. The apparent viscosity, intrinsic viscosity and apparent weight average molecular weight (Mw,a), root mean square radius of gyration <Rg>, hydrodynamic radius <Rh> and ratio of <Rg>/<Rh> were decreased with the increase in speeds of the waring blender. Its microstructure transformed from spatial network structure to independent of molecular aggregates. Shearing not only made the molecular chains of polymers fracture, but also made the polymer chains transform from stretch to curl.